Faktor-faktor yang Mempengaruhi Masyarakat untuk Menggunakan Mobile Payment pada Online Shop di Batam - Golan Hasan (Perkumpulan Dosen Manajemen Indonesia, 2020)
The purpose of this research is to find out what are the factors that influence behavioural intention to adopt in using mobile payment (m-payment). The factors are perceived usefulness variables, perceived ease of use, compability, subjective norms, perceived risk, perceived trust and perceived cost.The object of this research is an online shop at Batam. The population was community who had used a mobile payment while doing their online shopping. The total of questionnaires were 260 sheets.Based on the data processing using the SPSS program, perceived usefulness, perceived ease of use, compatibility, subjective norms, perceived risk, perceived trust and perceived cost affect the behavioral intention to adopt.